The Consistency of Essay Texts Found in Grade Eleven English E-Book Interlanguage to the English Context of Culture - Juita Triana (Universitas Muhammadiyah Semarang, 2017)
This study reveals the result of the research aimed at describing the consistency of essay texts found in grade eleven English E-book Interlanguage to the English context of culture. It shows how the generic structures displayed in the texts, and how the linguistic features serve the communicative purposes. This study uses descriptive qualitative research method. The finding shows that mostly the essay texts are compatible with the English context of culture, although some shortcomings are still appear. Expectedly, the result of the research will be a consideration for the progress of English teaching and learning in Indonesia especially encouraging the students to get better understanding on genres.